Comparison of EDCs removal in full and pilot scale membrane bioreactor plants: Effect of flux rate on EDCs removal in short SRT - Komesli, O. T.; Muz, M.; Ak, M. S.; Bakirdere, S.; Gokcay, C. F. (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2017)
Currently, it is estimated that over 1 billion people are short of adequate portable water and this is expected to increase to 2.5 billion in the year 2025. Membrane Bioreactors (MBR) are now accepted as important tools to extend the availability of water by facilitating the reuse of wastewaters. Sludge Retention Time (SRT) and liquid flux rate are the two most important parameters for controlling the MBR process. In this study, the removal of selected endocrine disrupter compounds (EDCs), diltiazem, progesterone, estrone (E-1), carbamazepine (Cbz) and acetaminophen (Acet), by one full scale (VRM) and one pilot scale (clear-box) MBR plants was investigated. During the study, sludge age was set at 10 days and the sludge concentration was fixed at about 5.0 g/L. The transmembrane pressure (TMP) got higher with either increasing flux or sludge concentration in the membrane chamber. Therefore, changing the flux from 13 to 30 L/m(2)-h in both plants caused enhancement in TMP from -25 to -300 mbar in the clear box and from 160 to over 350 in the full scale MBRs. It was understood that flux had very little effect on the removal of EDCs at very low concentrations. Moreover, diltiazem was completely removed in the full scale whereas no removal was achieved in the pilot scale. Estrone and progesterone were completely removed by biodegradation in both plants. Acetaminophen was completely removed in the full scale plant whereas over 95% removal was achieved in the pilot scale MBR. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Membrane bioreactor; Transmembrane pressure; Flux; Endocrine disrupter compounds; Suction time; WASTE-WATER TREATMENT; ENDOCRINE DISRUPTING COMPOUNDS; SEWAGE-TREATMENT PLANTS; PERSONAL CARE PRODUCTS; PHARMACEUTICAL RESIDUES; ESTROGENIC CHEMICALS; STW EFFLUENT; TRACE LEVELS; HORMONES; IDENTIFICATION; Environmental Sciences & Ecology